Determination of selected bisphenols, parabens and estrogens in human plasma using LC-MS/MS - Kolatorova Sosvorova, Lucie; Chlupacova, Tereza; Vitku, Jana; Vlk, Martin; Heracek, Jiri; Starka, Luboslav; Saman, David; Simkova, Marketa; Hampl, Richard (Talanta, 2017)
In this study, a novel liquid chromatography - tandem mass spectrometry method for the simultaneous determination of bisphenols (BPA, BPS, BPF, BPAF), parabens (methyl-, ethyl-, propyl-, butyl-, benzyl-paraben) and estrogens (estrone, estradiol, estriol) in human plasma is presented. Since all analytes possess the phenolic group, dansyl chloride derivatization was applied in order to gain high sensitivity. The method was validated according to FDA guidelines, and all validation requirements were satisfactory. The lower limits of quantifications were 41.6, 54.9, 43.5 and 150.8pg/mL for BPA, BPS, BPF and BPAF; 172, 149, 171, 134 and 202pg/mL for methyl-, ethyl-, propyl-, butyl- and benzyl-paraben; 10.5, 6.7 and 9.4pg/mL for estrone, estradiol and estriol, respectively. This is the first method allowing the determination of plasma bisphenols, parabens and estrogens in one run, and also the first determination of BPF levels in human plasma. The method was used to examine the plasma levels of healthy normospermic men, where three times higher plasma levels of BPF than BPA were found.
Keywords: Phenols; estrogeny; Endocrine disruptor; Alternative bisphenol; LC-MS/MS; Limit of Detection; Bisphenol A; limita detekce; Bisphenol F; Blood Chemical Analysis; fenoly; biochemická analýza krve; Paraben; Humans; Tandem Mass Spectrometry; Estrogens; parabeny; chromatografie kapalinová; Parabens; tandemová hmotnostní spektrometrie; Chromatography, Liquid; lidé